2014
DOI: 10.1159/000362422
|View full text |Cite
|
Sign up to set email alerts
|

De novo Renal Cell Carcinoma in a Kidney Allograft with Focus on Contrast-Enhanced Ultrasound

Abstract: The development of de novo renal cell carcinoma (RCC) in a transplanted kidney is a rare condition. Currently, this is the second case report of a 41-year-old man in whom carcinoma of a renal allograft was detected by contrast-enhanced ultrasound (CEUS). An abdominal CT scan was not conclusive enough to differentiate between septal enhancement of a cyst and a low vascularized tumor. CEUS confirmed a solid, homogeneously enhancing but hypoechoic and hypovascular lesion compared to the surrounding kidney parench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, in patients with kidney allografts, CEUS imaging can detect lesions not identified on CT [17]. On the contrary, another study showed de novo RCCs in kidney allograft patients with acquired cystic kidney disease that could not be detected using US, yet could be detected on native MRI [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in patients with kidney allografts, CEUS imaging can detect lesions not identified on CT [17]. On the contrary, another study showed de novo RCCs in kidney allograft patients with acquired cystic kidney disease that could not be detected using US, yet could be detected on native MRI [13].…”
Section: Introductionmentioning
confidence: 99%